Lycium barbarum polysaccharide promotes corneal Re-epithelialization after alkaline injury. (August 2022) - Wong, Ho Lam; Bu, Yashan; Chan, Yau Kei; Shih, Kendrick Co
Abstract: Chemical injury of the cornea results in epithelial defect and subsequent stromal scarring and infection. Our study aims to evaluate the effectiveness of pre-treatment of Lycium barbarum polysaccharide (LBP) in promoting corneal re-epithelialization after alkaline burn. The corneas of C57BL/6J mice were pre-treated with topical phosphate-buffered saline or LBP (0.2/2/20 mg/mL) for 7 days, following by 0.1M sodium hydroxide injury for 30 s and washing with distilled water for another 30 s. Area of epithelial defect and thickness of cornea were evaluated. Inflammatory cytokines and water channel expression levels were assessed using immunohistochemistry and Western blot. Compared to the injury group, mice with 2 mg/mL LBP pre-treatment revealed a significant decrease in fluorescein stained area after injury (p = 0.025), with increased epithelial layer thickness (p = 0.004). The corneal opacity was significantly reduced in the group with 2 mg/mL LBP pre-treatment followed by injury (p = 0.02). The expression of matrix metalloproteinase 12 (p = 0.033), platelet derived growth factor-BB (p = 0.031), and aquaporin 5 (p = 0.022) resulted in a decrease in expression level in group with 2 mg/mL LBP pre-treatment. Our results showed that 2 mg/mL LBP, with no apoptotic effect on corneal cells, promoted corneal epithelial growth and minimized disruption of the collagen architecture after injury in vivo. We suggest that LBP, as a natural Traditional Chinese Medicine, may potentially be a novel topical pre-treatment option for patients highly susceptible to ocular injury. Highlights: Persistent corneal epithelial defects and inflammation lead to irreversible corneal scar and visual loss. Lycium barbarum polysaccharide promotes corneal re-epithelialization and reduced pro-inflammatory cytokines secretion after injury.